Comparing Quality of Life and Postoperative Pain After Limited Access and Conventional Aortic Valve Replacement: A Randomized Clinical Trial. (9th April 2021) - Klop, Idserd D.; van Putte, Bart P.; Kloppenburg, Geoffrey T.; Sprangers, Mirjam A.; Nieuwkerk, Pythia T.; Klein, Patrick
Abstract : Objective : Limited access aortic valve replacement (LA-AVR) yields excellent results as an alternative to conventional surgical aortic valve replacement by full median sternotomy (C-AVR). However, robust data on quality of life (QoL) improvements and the differences in postoperative QoL and pain compared to C-AVR are lacking. We report the one-year results of the LImited access Aortic valve Replacement (LIAR) Trial. Methods : The LIAR-Trial is an investigator initiated, Dutch government sponsored, single center, randomized controlled trial comparing postoperative QoL and pain in patients undergoing LA-AVR through partial upper hemisternotomy (UHS) and C-AVR for symptomatic severe aortic valve stenosis. All patients were intended to have their native aortic valve replaced by a rapid deployment stented bioprosthesis (RDSBP). Primary outcome was cardiac related QoL, measured by the Kansas City Cardiomyopathy Questionnaire (KCCQ) at one, three, six and twelve months postoperatively. Secondary outcomes included generic QoL, postoperative pain, analgesic use and postoperative Complications. Results : A total of 161 patients were randomized. Per protocol analysis demonstrated significant differences in the primary outcome measures: estimated mean differences of both the Physical Limitations domain (2.22 points; 95%CI, 0.96 - 3.28; p=0.01) and the Total Symptom Score of the KCCQ (3.31 points; 95%CI, 0.30 - 6.31; p=0.031) demonstrated significantly increase improvement after LA-AVR compared to C-AVR. Regarding the secondary outcome measures: LA-AVR was associated with a significant increased improvement in the Overall Summary Score and Social Limitation domain of the KCCQ, Mental Health of the Short Form-36 and reduced postoperative pain. Operative times were significantly longer in the LA-AVR group. No significant differences were found regarding 30-day complication rate. Conclusions : LA-AVR through UHS with the use of a RDSBP is associated with an increased improvement in cardiac related QoL and reduced postoperative pain compared to C-AVR.